Comorbidity in idiopathic pulmonary fibrosis - what can biomarkers tell us?. (March 2020) - Alfaro, Tiago M.; Robalo Cordeiro, Carlos
Idiopathic pulmonary fibrosis (IPF) is characterized by progressive parenchymal scarring, leading to dyspnoea, respiratory failure and premature death. Although IPF is confined to the lungs, the importance of IPF comorbidities such as pulmonary hypertension and ischaemic heart disease, lung cancer, emphysema/chronic obstructive pulmonary disease, gastroesophageal reflux, sleep apnoea and depression has been increasingly recognized. These comorbidities may be associated with increased mortality and significant loss of quality of life, so their identification and management are vital. The development of good-quality biomarkers could lead to numerous gains in the management of these patients. Biomarkers can be used for the identification of predisposed individuals, early diagnosis, assessment of prognosis, selection of best treatment and assessment of response to treatment. However, the role of biomarkers for IPF comorbidities is still quite limited, and mostly based on evidence coming from populations without IPF. The future development of new biomarker studies could be informed by those that have been studied independently for each of these conditions. For now, clinicians should be mostly attentive to clinical manifestations of IPF comorbidities, and use validated diagnostic methods for diagnosis. As research on biomarkers of most common diseases continues, it is expected that useful biomarkers are developed for these diseases and then validated for IPF populations. The reviews of this paper are available via the supplemental material section.